Іmproving efficiency of process of grinding grain in preparation of feed - Boltianskyi, Borys; Болтянський, Борис Володимирович; Болтянский, Борис Владимирович; Boltianska, Larysa; Болтянська, Лариса Олексіївна; Болтянская, Лариса Алексеевна (НУБіП України, 2021)
EN : As a result of theoretical and experimental studies, it is recognized that increasing the effectiveness of the preparation of mixed fodder in conditions of salt-corporate enterprises can be achieved on the basis of the use of gravitational, inertial and centrifugal impact on loose feed materials by creating new working bodies of intensifying action, which Perform separation (cleaning), grinding, dosage and mixing of mixed fodder components. Increasing grain grinding efficiency can be due to a multi-penalaneous grinding and removing crushed particles from a crushing chamber when converted from one degree of grinding to another, which means no reincarnation of the material due to a decrease in the mass of the circulating load. And for effective grinding grain, it is directed to its movement towards the working body for direct impact. Moreover, a direct blow must be carried out with thin moaters, for example, in the form of fingers or rods.
Keywords: cleaning; grinding; crushing chamber; іncreasing grain grinding